2020
DOI: 10.1155/2020/1230513
|View full text |Cite
|
Sign up to set email alerts
|

Six-Gene Signature Associated with Immune Cells in the Progression of Atherosclerosis Discovered by Comprehensive Bioinformatics Analyses

Abstract: Background. As a multifaceted disease, atherosclerosis is often characterized by the formation and accumulation of plaque anchored to the inner wall of the arteries and causes some cardiovascular diseases and vascular embolism. Numerous studies have reported on the pathogenesis of atherosclerosis. However, fewer studies focused on both genes and immune cells, and the correlation of genes and immune cells was evaluated via comprehensive bioinformatics analyses. Methods. 29 samples of atherosclerosis-related gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“… 29 The progression of carotid atherosclerosis is related to CD53. 30 In the present study, the aim was to focus on DEGs between atheroma plaque and control samples. However, due to lack of experimental validation, it is not clear whether these genes are causal or merely markers.…”
Section: Discussionmentioning
confidence: 99%
“… 29 The progression of carotid atherosclerosis is related to CD53. 30 In the present study, the aim was to focus on DEGs between atheroma plaque and control samples. However, due to lack of experimental validation, it is not clear whether these genes are causal or merely markers.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly expressed on the membranes of immune cells, where it helps regulate many of their functions, including adhesion, migration, and cell fusion ( Dunlock, 2020 ), and plays an important role in antigen presentation. Many studies have shown that CD53 is increased in obese and inflammatory tissues, and regulating its expression may be an effective treatment for obesity with complications ( Nair et al, 2005 ; Zhao et al, 2020 ). PLEK is the major protein kinase C substrate phosphorylated in diabetic macrophages, where a 30% reduction in PLEK can inhibit TNFα secretion by 80% ( Ding et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the co-inhibitory CTLA4 reduced atherosclerotic burden and plaque inflammation in Apoe − /− mice and resulted in a profound decrease in effector T cells [107]. In human atherosclerotic plaques, expression of CD80/CD86 is correlated with plaque vulnerability [108], and a recent bioinformatics study identified CD86 as one out of 6 genes driving immune cell activation in human atherosclerosis [109] . Patients suffering from coronary artery disease and those at risk of stroke displayed an increased expression of CD80 and CD86 on monocyte-derived DCs and B cells [110].…”
Section: Cd28/ctla4 -Cd80/cd86mentioning
confidence: 99%